Modifikasi Alat Pemindah dan Penyortir Material Logam dan Non Logam sebagai Media Pembelajaran Mahasiswa di Laboratorium Sistem Kontrol - Wiguna, Rifki Arya; Rochadian, Okpina; Putra Jaya, Agil (PPPM Polimarin, 2024)
Politeknik Maritim Negeri Indonesia has a model of a tool for moving materials which is controlled using a PLC, but this model is no longer operational and some of its components are broken. The tool is used as a learning media for students majoring in engineering in the field of control systems and PLCs. Tool repairs and modifications are made by adding metal and non-metal material sorters. The problems that arise are how to form a series of ladder diagrams to work in one cycle and the vacuum pressure of air to lift metal and non-metal materials. The method in this study uses research and development (Research and Development). The equipment and materials in this study used the PLC Omron CP1E 20 I/0 and the sample materials were aluminium and nylon with a diameter of 30 and a thickness of 8 mm. The conclusion is that this tool can work using the ladder diagram that has been made in one cycle and the best pressure is 4 bar.